Pengaruh Motivasi Kerja Dan Kemampuan Kerja Terhadap Kinerja Karyawan Di Hotel Lembang Rantepao Kabupaten Toraja Utara - Hasna Pabate; Althon K. Pongtuluran (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The Effect of Work Motivation and Work Ability on Employee Performance at Hotel Lembang Rantepao, North Toraja Regency. The aims to determine the results of the influence of work motivation and work ability on employee performance at the Lembang Rantepao Hotel in 2022. The method used in this study was a survey and used data collection methods through filling out questionnaires and implement and develop data to be processed using SPSS. The type of research used in this research is quantitative research. The type of data used is primary data in the form of information from the object of research through the distribution of research questionnaires at the Lembang Hotel. The conclusion of this study shows that there is an influence of work motivation variable on employee performance but there is no effect of work ability on employee performance at Lembang Hotel.